Mission, Reunion and the Anglican Communion: The ‘Appeal to All Christian People’ and approaches to ecclesial unity at the 1920 Lambeth Conference - Methuen, Charlotte (Ecclesiology, 2020)
This article explores the understanding of unity articulated in the ‘Appeal to all Christian People’ issued by the 1920 Lambeth Conference of Anglican bishops. It first examines the expression of the Appeal’s vision in terms of organic unity and mutual recognition, the way that this developed through the drafting process and how this vision related to later Anglican approaches to unity. It then explores the relationship of the Appeal to the Lambeth Quadrilateral of 1888, particularly with respect to the episcopate, arguing that the Appeal took an ambiguous approach to episcopacy which was in tension with the language of mutual recognition. Finally, acknowledging that the overarching theme of the 1920 Lambeth Conference was ‘fellowship’, the article considers the Appeal’s vision of unity in the context of the approach to unity taken by the 1920 Lambeth Conference more widely, including the Conference’s other ecumenical resolutions, and its resolutions on mission and the Anglican Communion and the bishops’ Encyclical Letter, particularly its approach to international relations. The article concludes that, while the vision of organic unity that was articulated in the Appeal was reflected in the conference’s resolutions on mission, in other aspects of its work the 1920 Lambeth Conference tended to take a federal approach to unity and fellowship and was thus not fully consistent.